Hybrid design of optimal shunt capacitor allocation and reconfiguration of radial distribution systems considering techno-economic benefits - Ifeoluwa Olajide Fajinmi; Gafari Abiola Adepoju; Sunday Adeleke Salimon; Kareem M. AboRas; Oluwaseyi Wasiu Adebiyi; Olubunmi Onatoyinbo; Mohammad Khishe; Pradeep Jangir; Wulfran Fendzi Mbasso (Results in Engineering)
Efficient power delivery is crucial for power distribution systems, prompting utilities to consistently seek out new technologies to improve their performance. Managing power loss and cost efficacy stands out as a critical concern, directly impacting systems efficiency. Hence, this study provides an innovative method for the performance enhancement of radial distribution networks (RDNs) through simultaneous reconfiguration and Shunt Capacitor (SC) allotment utilizing a newly developed Dandelion Optimizer (DO) and a novel objective function. The main aim of the optimization process is to maximize economic benefits while also assessing technical advantages. Technical benefits include real power loss, Average Voltage Stability Index (AVSI), and Voltage Profile Index (VPI), while economic benefits involve evaluating cost reductions due to decreased power purchased and losses, as well as the SC and switching costs spanning a 20-year planning period. Tests were conducted on IEEE 33- and 69-bus RDNs using the suggested methodology under various scenarios, including reconfiguration, SC integration, and synchronous reconfiguration with SC allocation, and the model was simulated using MATLAB software. The optimal solution was achieved by simultaneously reconfiguring and allocating SCs to maximize total cost benefits. For the 33-bus system, this resulted in power loss, AVSI, VPI, and total cost-benefit values of 82.84 kW (62.90 % reduction), 0.9566 p.u., 1.9190 p.u., and $ 773 752.85, respectively, while for the 69-bus system, the corresponding values were 43.8 kW (80.51 % reduction), 0.9874 p.u., 2.4680 p.u., and $ 1.1347 million. Comparing the technique with other methods, its effectiveness was established, and it was shown to perform better with power loss reduction chosen as assessment metric.